IMPLEMENTASI SUPPLY CHAIN MANAGEMENT PADA E-COMMERCE SEBAGAI STRATEGI PENGEMBANGAN UMKM JAJANAN DODOL KHAS BULELENG - I Wayan Agus Surya Darma; I Gusti Agung Indrawan; Ni Putu Sutramiani (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTPenglatan Village is a village that is the biggest dodol production center of Buleleng in the largestdistrict of Buleleng which is distributed to all regencies in Bali, even Buleleng dodol is also an icon oftypical souvenirs of Buleleng to be taken outside of Bali. Conventional trading has been carried out bymicro and small and medium enterprises (UMKM) entrepreneurs in the village of Penglatan who arecraftsmen of Buleleng dodol. Dodol craftsmen in the village of Penglatan, which is a home industrythat sells dodol products to collectors, then collectors distribute dodol products typical of Buleleng toall districts in Bali. This causes the home industry in the village of Penglatan difficult to developbecause it can not handle direct requests. Another problem faced is the difficulty of the craftsmen incalculating the need for raw materials in producing dodol typical of Buleleng when there is an order.Implementation of supply chain management in e-commerce that was developed to manage the supplyof dodol raw materials in accordance with orders that enter the system. This is expected to help dodolcraftsmen in the village of Penglatan in determining the need for raw materials needed to produceorders and provide electronic-based trading media. Determination of raw material requirements forproducing dodol is calculated by applying the concept of master requirements planning. Thedeveloped system can help MSMEs in managing sales transactions and calculating raw materialrequirements in producing dodol.Keywords: Supply Chain Management, Material Requirement Planning, E-Commerce, Dodol KhasBuleleng.ABSTRAKDesa Penglatan merupakan desa yang menjadi sentra produksi dodol khas Buleleng terbesar dikabupaten Buleleng yang disalurkan ke seluruh kabupaten di Bali, bahkan dodol Buleleng jugamenjadi ikon oleh-oleh khas Buleleng untuk dibawa ke luar Bali. Perdagangan secara konvesionaltelah dilakukan oleh pelaku Usaha Mikro Kecil dan Menengah (UMKM) di desa Penglatan yangmenjadi pengrajin dodol Buleleng. Pengrajin dodol di desa Penglatan yang merupakan industri rumahtangga yang menjual produk dodolnya ke pengepul, kemudian pengepul mendistribusikan dodol khasBuleleng ke seluruh kabupaten di Bali. Hal ini menyebabkan industri rumah tangga di desa Penglatansulit berkembang karena tidak bisa menangani permintaan langsung. Permasalahan lainnya yangdihadapi adalah sulitnya pengrajin dalam memperhitungkan kebutuhan bahan baku dalammemproduksi dodol khas Buleleng ketika ada pesanan. Implementasi supply chain management padae-commerce yang dikembangkan untuk mengelola pasokan bahan baku dodol sesuai dengan pesananyang masuk ke sistem. Hal ini diharapkan dapat membantu pengrajin dodol di desa Penglatan dalammenentukan kebutuhan bahan baku yang diperlukan dalam memproduksi pesanan dan memberikanmedia perdagangan berbasis elektronik. Penentuan kebutuhan bahan baku untuk memproduksi dodoldihitung dengan menerapkan konsep master requirement planning. Sistem yang dikembangkan dapatmembantu UMKM dalam mengelola transaksi penjualan dan menghitung kebutuhan bahan bakudalam memproduksi dodol.Kata kunci: Supply Chain Management, Material Requirement Planning, E-Commerce, Dodol KhasBuleleng.